Psychological and moral determinants in accepting cheating and plagiarism among university students in Poland - Chudzicka-Czupała, Agata (Department of Psychology, University of Wrocław, 2014)
The study investigates the psychological and moral acceptance of cheating and plagiarism among university students in Poland. A sample of 285 students participated. Results demonstrate that the locus of control, justice sensitivity, and some individual ethical philosophical dimensions are significant predictors for accepting dishonest behaviour. My research results support the basic theoretical arguments that point out the role of acceptable individual conditions for cheating and plagiarism. The research offers implications for the practice of moral awareness and for some possible training for university students.
Keywords: locus of contro; justice sensitivity; unethical behaviour; academic dishonesty; moral philosophy